2005
DOI: 10.1111/j.1741-3729.2005.00322.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Coparenting During Infancy*

Abstract: This study examined family characteristics associated with the coparenting behavior of 60 parents with an 11-to 15-month-old infant (30 boys, 30 girls) during a structured triadic play session. Mothers reported on family demographics, social support, and child temperament. Both parents reported on their self-esteem and childrearing beliefs. Fathers displayed more supportive coparenting behavior than mothers. Mothers' intrusive coparenting behavior differed based on the number of children, parent's employment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
92
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 50 publications
12
92
1
2
Order By: Relevance
“…Of the various themes on this topic the three most common variables of interest include: marital satisfaction, the degree and quality of co-parenting, and fathers' working model of their romantic relationship (Caldera & Lindsey, 2006;Cowan & Cowan, 2009;Floyd, Gilliom, & Costigan, 1998;Lindsey, Caldera, & Colwell, 2005;McHale & Alberts, 2003). This work is extended in the current collection of studies through examinations of child-father attachment relationships within a family systems framework which takes into account both individual and family transactional processes.…”
Section: Correlates and Consequences Of Father Attachment In Contextmentioning
confidence: 99%
“…Of the various themes on this topic the three most common variables of interest include: marital satisfaction, the degree and quality of co-parenting, and fathers' working model of their romantic relationship (Caldera & Lindsey, 2006;Cowan & Cowan, 2009;Floyd, Gilliom, & Costigan, 1998;Lindsey, Caldera, & Colwell, 2005;McHale & Alberts, 2003). This work is extended in the current collection of studies through examinations of child-father attachment relationships within a family systems framework which takes into account both individual and family transactional processes.…”
Section: Correlates and Consequences Of Father Attachment In Contextmentioning
confidence: 99%
“…However, several maternal and paternal traits are positively correlated, and thus, although we relied on one parent's characteristics, we may expect that these variables also capture some information about the other parent. In particular, the resident parent's age at time of interview and her/his educational level and employment status are controlled for, following suggestions made in previous studies (Cheadle, Amato, and King 2010;Lindsey, Caldera, and Colwell 2005). Also, the time passed since the de facto separation (chosen as marking the end of the marriage, following the approach used in other Italian studies; for example, Meggiolaro and Ongaro 2008) is taken into account, because children's relationships with their non-resident parents are stronger when less time has elapsed since separation (Le Bourdais, Juby, and Marcil-Gratton 2002;Aquilino 2006).…”
Section: Modeling Non-resident Parent-child Contactmentioning
confidence: 99%
“…Co-parenting, which is distinct from individual parenting style, can be measured on two dimensions, supportiveness and intrusiveness, and is the proximal link accounting for the impact of the marital relationship on parenting (McHale & Alberts, 2003). Both co-parenting and the quality of the marital relationship contribute to the quality of the parent-child relationship (Caldera & Lindsey, 2006;Floyd, Gilliom, & Costigan, 1998;Lindsey, Caldera, & Colwell, 2005). Lindsey et al (2005) found that parents with similar childrearing beliefs were likely to be more supportive of one another's parenting, and fathers tended to be more supportive in co-parenting than mothers.…”
Section: Co-parenting and Shared Childrearing Beliefsmentioning
confidence: 97%